A global meta‐analysis of soil organic carbon response to corn stover removal. Issue 10 (2nd July 2019) - Xu, Hui; Sieverding, Heidi; Kwon, Hoyoung; Clay, David; Stewart, Catherine; Johnson, Jane M. F.; Qin, Zhangcai; Karlen, Douglas L.; Wang, Michael
Abstract: Corn ( Zea mays L.) stover is a global resource used for livestock, fuel, and bioenergy feedstock, but excessive stover removal can decrease soil organic C (SOC) stocks and deteriorate soil health. Many site‐specific stover removal experiments report accrual rates and SOC stock effects, but a quantitative, global synthesis is needed to provide a scientific base for long‐term energy policy decisions. We used 409 data points from 74 stover harvest experiments conducted around the world for a meta‐analysis and meta‐regression to quantify removal rate, tillage, soil texture, and soil sampling depth effects on SOC. Changes were quantified by: (a) comparing final SOC stock differences after at least 3 years with and without stover removal and (b) calculating SOC accrual rates for both treatments. Stover removal generally reduced final SOC stocks by 8% in the upper 0–15 or 0–30 cm, compared to stover retained, irrespective of soil properties and tillage practices. A more sensitive meta‐regression analysis showed that retention increased SOC stocks within the 30–150 cm depth by another 5%. Compared to baseline values, stover retention increased average SOC stocks temporally at a rate of 0.41 Mg C ha −1  year −1 (statistically significant at p  < 0.01 when averaged across all soil layers). Although SOC sequestration rates were lower with stover removal, with moderate (<50%) removal they can be positive, thus emphasizing the importance of site‐specific management. Our results also showed that tillage effects on SOC stocks were inconsistent due to the high variability in practices used among the experimental sites. Finally, we conclude that research and technological efforts should continue to be given high priority because of the importance in providing science‐based policy recommendations for long‐term global carbon management. Abstract : Excessive corn stover removal for livestock, bioenergy, or other uses can decrease soil organic C (SOC) stocks and deteriorate soil health. Stover removal effects on SOC were evaluated by synthesizing stover harvest experiments conducted around the world. Removal generally decreased C sequestration rates, but a moderate harvest (<50%) may sustain a positive sequestration rate and SOC stocks. Tillage did not consistently change SOC stocks due to high variability in the practices reported in the literature. We conclude that research and technological efforts to identify sustainable corn stover removal rates should continue and be given high priority.